Information Quality, Social Friendship and Social Interaction in Predicting Web Usage and Online News Readers’ Understanding - Yusdiana Yusdiana; Bernardinus Maria Purwanto; Sahid Susilo Nugroho (Universitas Muhammadiyah Yogyakarta, 2023)
This research aims to reveal information quality, social friendship, and social interaction in predicting web usage and understanding of online news readers and also to reveal that web usage predicts online news readers’ understanding. This quantitative research uses an online survey design based on a purposive sampling technique using 423 respondents who are active readers of online news. The data in the study were analyzed using SEM Amos and SPSS 21. The results and findings showed that information quality and social interaction could positively and significantly predict web usage and understanding of online readers. Web usage could also predict online reader understanding positively and significantly. Social friendships could not predict web usage and reader understanding of online news based on research results. The theoretical implication of the research aims to fill the gap in the existing literature on information quality and social interaction that can explain web usage and understanding of online newsreaders and web usage as a predictor to explain the effect of comprehension as an individual’s intended media use. The practical implication of this study is that websites as news sources must pay attention to information and features that are more attractive to readers or potential online news readers.